Perilaku Self Injury Pada Siswa kelas VIII Di Sekolah Menengah Pertama - Safitri, Firda; Nuraini, Nuraini (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to analyze the behavior of Non-Suicidal Self-Injury (NSSI) among eighth-grade students at SMPN 102 Jakarta by referring to the Grand Theory of Parks (2012), which conceptualizes self-injury as a form of self-directed violence carried out consciously. The study is grounded in the gap of understanding regarding the psychosocial aspects of individuals who engage in self-injury as a response to emotional distress. This research employs a qualitative approach with a descriptive method and utilizes data triangulation techniques, including in-depth interviews, observation, and documentation, involving three primary subjects identified as engaging in self-injurious behavior, as well as six supporting informants comprising teachers, siblings, and close friends. The study was conducted from March to May 2024. The findings reveal that the self-injury behavior of the subjects aligns with Parks’ conceptualization, including: a history of trauma, a tendency to conceal personal problems, the interpretation of physical pain as an outlet for negative emotions, and low self-esteem. Contributing factors include family conflicts, dysfunctional interpersonal relationships, and past traumatic experiences. Social support received by the subjects was predominantly from peers, while family roles tended to be passive or unresponsive to the subjects’ conditions. This study emphasizes the importance of early detection of self-injurious behavior patterns and the need to strengthen school-based psychosocial approaches that integrate the roles of school counselors, families, and professional therapists in fostering students’ self-control and self-confidence.